Secondary Education in Manipur A Status Study - Angom, Sangeeta; Devi, Leisangthem Binita (JOURNAL OF INDIAN EDUCATION, 2012)
Education in its broadest sense of development of youth is the most crucial input for empowering people with skills and knowledge and giving them access to productive employment in future. The Eleventh Plan places the highest priority on education as a central instrument for achieving rapid and inclusive growth. Elementary education has received a major push in the Tenth Plan through the Sarva Shiksha Abhiyan (SSA). In the view of the demands for rapidly changing economy, a mere eight years of elementary education would be grossly inadequate for the young children to acquire necessary skills to compete in the job market. Therefore, a mission for secondary education is essential to consolidate the gains of SSA and to move forward in establishing a knowledge society. Moreover, secondary education serves as a bridge between elementary and higher education, the success of SSA thrown open the challenge of expanding access to secondary education through its universalisation. With this context, the present paper aims to study the present status of secondary education in Manipur. It also tries to capture the major gaps in enrolment, dropouts and school retention at secondary level. Finally, the paper also attempts to examine the schemes and policy taken up by the State Government for universalisation of secondary education in Manipur. The paper is based mainly on secondary data collected from Selected Educational Statistics, Census Report, Statistical Report of Manipur, DISE data, data from Directorate of Education(s), Manipur, Board of Secondary Education, Manipur and RMSA, Manipur.